Storytelling for Brand Awareness on Instagram: The Case of AGAVILab in the Biotechnology Sector - Annahlka, Oriell; Diniati, Anisa (JURNAL KOMUNIKASI INDONESIA, 2025)
Brands, including AGAVILab, have implemented an Instagram content management strategy to address the challenges of building brand awareness, which is particularly important for startups not yet well-known to the public. Therefore, the company needs to enhance its efforts to create brand awareness, which is crucial for consumers when choosing products. As a startup that provides biotechnology research materials, AGAVILab is not yet well-known to the public. Therefore, the company needs to enhance its efforts to create brand awareness, which is crucial for consumers when choosing products. This research aims to describe how AGAVILab manages its Instagram content to build brand awareness using storytelling techniques. The study employs Regina Luttrell's Circular Model of SoMe for Social Communication to explain the content management process and Maylanny Christin's Triangle of Storytelling to illustrate the relationships among the key components in storytelling content. The research follows a descriptive qualitative approach conducted over nine months, from April to December 2023. The primary sources include social media monitoring of the @agavi.lab Instagram account, interviews, and literature reviews. The findings reveal that AGAVILab's content management strategy aims to increase brand awareness and public trust in its products. This strategy comprises four stages: analyzing the Instagram account, designing and producing content, maintaining audience engagement, and evaluating performance. AGAVILab seeks to establish a strong brand presence and foster engagement with its target audience through this approach. The study provides practical implications for startups in niche industries seeking to build digital brand visibility and offers a theoretical contribution by contextualizing social media storytelling as an effective communication strategy within the biotechnology sector.